Peran Sistem Informasi dan Badan Usaha Milik Desa dalam Pemberdayaan Ekonomi Masyarakat Muslim Yang Berkelanjutan - Khotibul Umam; Ahmad Tubagus Surur; Syamsuddin (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2025)
This study aims to identify solutions to the challenges of economic development for the Muslim community in Wiroditan Village, Pekalongan Regency, through the optimisation of the village government information system and the transformation of the Village-Owned Enterprise. The research method used is a qualitative approach using secondary data. Data was collected through literature review to understand the phenomena experienced by the research subjects in a holistic manner. Data analysis was conducted systematically, focusing on explaining the facts obtained from the data sources, using interactive and continuous qualitative analysis techniques. The research results indicate that optimising the Village Information System and transforming the Village-Owned Enterprise are key factors in accelerating economic development in Wiroditan Village. This study contributes to the importance of the Village Information System's function in improving access to information and transparency, while the Village-Owned Enterprise expands business opportunities and community participation.